Biodiesel Production from Waste Cooking Oil using Electrostatic Method - Susumu Susumu; Rusdianasari Rusdianasari; Syahirman Yusi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
Biodiesel (methyl ester) produced from trans esterification of waste cooking oil is a potential material to replace diesel fuel. The biodiesel can be obtained by using electrostatic method equipped with fixed distance electrode 1.5 cm and voltage at 12 volts. Coagulation of particle process i.e. glycerin drops in biodieselglycerinmixture was based on electrical field. Reactants used were methanol over KOH catalyst and temperature was set at 60 C. The residence time was varied as well as methanol to waste cooking oil ratio. Analysis result shows the process was able to obtain yield up to 83.3%. The quality of biodiesel produced was tested and satisfy the requirement according to National Standard of Indonesia (SNI), i.e. density 0.8594 mg/mL (compared to SNI: 0.85-0.90 mg/mL), flash point 191 C (SNI min 100 C), water content 0.0342% (SNI max 0.05%) and viscosity at lower limit 2.31 cSt. According to SNI 7182-2015 the above value meets the specified standard.